Hepatocellular carcinoma cells surviving doxorubicin treatment exhibit increased migratory potential and resistance to doxorubicin re-treatment in vitro - Buschauer, Sebastian; Koch, Andreas; Wiggermann, Philipp; Mueller, Martina; Hellerbrand, Claus (Oncology Letters, 2018)
Transarterial chemoembolization (TACE) is an established therapeutic approach for the treatment of hepatocellular carcinoma (HCC). Although patients who undergo TACE may have prolonged survival, there are indications that the malignancy of residual HCC tissue can increase subsequent to the procedure. Although hypoxia, which occurs during TACE due to ischemia, is known to contribute to angiogenesis, little is known with regard to the undesirable effects of chemotherapeutic agents on residual HCC cells. Doxorubicin is one of the most commonly used drugs in TACE. The aim of the present study was to analyze alterations in Hep3B and HepG2 human HCC cell lines surviving doxorubicin treatment in vitro. Initially, the toxic concentration range was determined, and doxorubicin was subsequently applied in concentrations that killed >80% of the HCC cells. During the first days subsequent to treatment, surviving cells had higher expression levels of the epithelial-mesenchymal transition marker SNAIL, and exhibited increased migratory activity compared with control cells. At 3 weeks after the first doxorubicin treatment, surviving HCC cells tolerated significantly higher doxorubicin concentrations compared with control cells. As a potential explanation for this doxorubicin resistance, significantly increased mRNA expression levels of ATP-binding cassette ABCB1 (multidrug resistance protein 1) and ABCC1 (multidrug resistance-associated protein 1) were observed by reverse transcription-quantitative polymerase chain reaction. In summary, these findings indicate that, following TACE treatment, hypoxia as well as doxorubicin may induce a more malignant phenotype in surviving HCC cells and decrease susceptibility to further chemotherapeutic treatment.
EVALuna2:35811